Comportamiento agronómico de tres híbridos de coliflor (Brassica oleracea L.Var. Botrytis) sembrada con dos distanciamientos de siembra en la zona de La Libertad, provincia del Carchi - Jiménez Guerrero, Fernando Alejandro (2013)
This research was conducted in Agroforestry Cooperative Alejandro Almeida, sector San Tander of the parish of La Libertad, Canton Espejo Carchi Province, in order to evaluate the agronomic performance of three hybrids of cauliflower planted two seed spacings identify the largest hybrid cauliflower production, determine the most suitable plant density for growing and economically analyze treatments. Design was used randomized complete block (RCBD) with factorial arrangement (varieties x dose) with four replications and six treatments. The total test area was 525 m2 to 12,00 m2 experimental plots. Variables were evaluated, plant height, stem diameter, number of leaves, number of pellets, pellet diameter at harvest, average weight of the pellet-harvest field performance. All variables were subjected to analysis of variance, using the Tukey test at the 0.05 level of significance to determine the difference between the means of the study factors. The experimental results determined that: the best agronomic performance in plant height, stem diameter was presented by the Kangoo range with distance 0.50 x 0.50 m), the number of pellets per plot and diameter pellets net Kamgoo with planting distance 0.40 x 0.40 m), while in pellet weight and performance Nevada planting distance 0.50 x 0.50 m) was superior to other treatments. The three varieties tested Kangoo, Toccata and Nevada showed the same production. The planting distance 0.50 x 0.50 m) is the best in productivity growth in the two varieties.